Kekuatan Keunikan Produk dan Word Of Mouth terhadap Keputusan Pembelian - Ibnu Agung Permana; Asep M. Ramdan; Faizal Mulia Z (Journal of Management and Bussines (JOMB), 2019)
The purpose of this study was to determine the uniqueness of the product and word of mouth towards purchasing decisions at the UMKM UMKM Sukugumi Sugema UMKM. The research method used by the authors in this study used a system of random sampling where the authors distributed questionnaires to 75 consumers. The analysis technique used by the writer is using multiple linear regression analysis techniques, multiple correlation coefficient and determination coefficient. And to test the hypothesis the author uses a partial statistical test (t test) and a simultaneous test (f test). The results of the study using the determination coefficient test shows the value (Adjuster R2) of 0.749 which means the influence of product uniqueness and word of mouth on purchasing decisions is 76% and 24% influenced by other factors not examined. In addition, testing multiple correlation coefficients shows an R value of 0.869, which means there is a strong relationship between product uniqueness and word of mouth towards purchasing decisions. Based on the results of the F test that has been done, the sig value is found. 0,000 <0,05. Conclusions, product uniqueness and word of mouth partially have a significant effect on purchasing decisions. Keywords: Product Uniqueness, Word Of Mouth, Purchasing Decision.